Aerodynamic effect of windbreak on the crosswind phenomenon on a high-speed train - Harinaldi Harinaldi; Naufal P Ramadhan (Prosiding SNTTM, 2025)
Crosswind greatly affects the aerodynamic performance and operational safety of the high-speed train. Windbreak is one of the windproof facilities commonly used for high-speed trains in windy areas. This study aims to see how variations in windbreak height (3.8 m; 4.4 m; and 5.2 m) can affect the aerodynamic performance of high-speed trains. 3 aerodynamic coefficients (drag, lift, and rolling moment) of the HST were compared when the train passed the track under the same conditions using the ANSYS FLUENT CFD simulation. Sudden changes in aerodynamic loads can be seen from the visualization of the pressure contour. First, the aerodynamic coefficient of the train will decrease significantly when the train begins to enter the windbreak. Second, the ‘IN’ process of the windbreak track has a larger aerodynamic load fluctuation than the ‘OUT’ process. Third, the height of the windbreak does not significantly change the trend of the aerodynamic coefficient graph, there is only a phase difference and the magnitude of the amplitude formed. The highest average drag and lift coefficient occurs at a height of 5.2 m, which is 0.29 and 0.011. Meanwhile, the highest average rolling moment coefficient occurs at a windbreak height of 3.8 m, which is 0.0028